2024
DOI: 10.1038/s41467-024-44845-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Schwann cells set perceptual thresholds for touch and selectively regulate mechanical nociception

Julia Ojeda-Alonso,
Laura Calvo-Enrique,
Ricardo Paricio-Montesinos
et al.

Abstract: Previous work identified nociceptive Schwann cells that can initiate pain. Consistent with the existence of inherently mechanosensitive sensory Schwann cells, we found that in mice, the mechanosensory function of almost all nociceptors, including those signaling fast pain, were dependent on sensory Schwann cells. In polymodal nociceptors, sensory Schwann cells signal mechanical, but not cold or heat pain. Terminal Schwann cells also surround mechanoreceptor nerve-endings within the Meissner’s corpuscle and in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…Nevertheless, Shin et al [ 14 , 15 ] observed the presence of PIEZO1 and PIEZO2 in both the axon and non-neuronal cells of rat CEOCs, while Yamanishi and Iwabuchi [ 20 , 21 ] revealed PIEZO2 expression in both the axon and terminal glial cells of human lanceolate nerve endings. This double cellular localization of mechano-gated protein in the axons and associated terminal glial cells of sensory corpuscles is of great interest because evidence is being accumulated that not only axons but also non-neuronal cells participate in touch detection [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Shin et al [ 14 , 15 ] observed the presence of PIEZO1 and PIEZO2 in both the axon and non-neuronal cells of rat CEOCs, while Yamanishi and Iwabuchi [ 20 , 21 ] revealed PIEZO2 expression in both the axon and terminal glial cells of human lanceolate nerve endings. This double cellular localization of mechano-gated protein in the axons and associated terminal glial cells of sensory corpuscles is of great interest because evidence is being accumulated that not only axons but also non-neuronal cells participate in touch detection [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%